2014
DOI: 10.22227/2305-5502.2014.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Parameters of Macrofragment Soils in Soil Dams

Abstract: Сделана попытка обобщить результаты стабилометрических испытаний крупнообломочных грунтов, выполненных другими авторами, а также дать рекомендации по определению параметров нелинейных моделей грунтов. Даны значения модулей объемной деформации гравийно-галечникового грунта и горной массы. Показано, что зависимость начальных модулей сдвига от напряжения обжатия может быть описана степенной формулой. Подтверждено предложение профессора Л.Н. Рассказова о возможности описания объемной деформации при контракции чере… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…The accumulation of the field monitoring data of the deformation of built rockfill dams enabled Pinto and Marques [14], Hunter [15], Fitzpatrick 11 to perform behavior analyses of the rockfill in real conditions. By the moment, much more monitoring data have been accumulated [16][17][18][19][20]. In papers [21][22][23], by means of numerical modeling a so-called back-analysis All those studies found out that the deformation modulus of the rockfill is different at accommodation of the own weight load and the hydrostatic pressure.…”
Section: Comparison Of the Results Of Laboratory Tests And Field Monimentioning
confidence: 99%
See 3 more Smart Citations
“…The accumulation of the field monitoring data of the deformation of built rockfill dams enabled Pinto and Marques [14], Hunter [15], Fitzpatrick 11 to perform behavior analyses of the rockfill in real conditions. By the moment, much more monitoring data have been accumulated [16][17][18][19][20]. In papers [21][22][23], by means of numerical modeling a so-called back-analysis All those studies found out that the deformation modulus of the rockfill is different at accommodation of the own weight load and the hydrostatic pressure.…”
Section: Comparison Of the Results Of Laboratory Tests And Field Monimentioning
confidence: 99%
“…Веденеева (СССР) для испытаний грунтов применялся стабилометр ПТС-300, в котором образец грунта имеет диаметр 300 мм и высоту 650 мм. На этом приборе проводились испытания модельных грунтов каменной наброски плотин Тери, Зарамагских ГЭС [18].…”
Section: описание лабораторных испытаний каменной наброскиunclassified
See 2 more Smart Citations
“…Coarse-clastic soils are one of the most promising building materials in the eld of earth dam construction. Building materials for such structures can more often be destroyed [10][11][12]. As is known, coarse-clastic soils are widely used for supporting the prism of rock and earth structures and occupy an average of 70% of the total volume of the dam [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%